2007
DOI: 10.1177/13670069070110040201
|View full text |Cite
|
Sign up to set email alerts
|

Heritage speaker competence differences, language change, and input type: Inflected infinitives in Heritage Brazilian Portuguese

Abstract: It has been argued that colloquial dialects of Brazilian Portuguese (BP) have undergone significant linguistic change resulting in the loss of inflected infinitives (e.g., Pires, 2002, 2006). Since BP adults, at least educated ones, have complete knowledge of inflected infinitives, the implicit claim is that they are transmitted via formal education in the standard dialect. In the present article, I test one of the latent predictions of such claims; namely, the fact that heritage speakers of BP who lack formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
187
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 26 publications
(38 reference statements)
9
187
2
3
Order By: Relevance
“…First, our data directly support claims made in the literature for over a decade that have, to date, not been sufficiently evidenced empirically. Sorace (2004) and Rothman (2007) independently suggested that some HS differences might be most accurately explained by them not having access to education in the standard variety and thus literacy in the HL. However, tangible evidence to support such a suggestion was extremely limited at the time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our data directly support claims made in the literature for over a decade that have, to date, not been sufficiently evidenced empirically. Sorace (2004) and Rothman (2007) independently suggested that some HS differences might be most accurately explained by them not having access to education in the standard variety and thus literacy in the HL. However, tangible evidence to support such a suggestion was extremely limited at the time.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has challenged this assumption (e.g., Kupisch 2013; Kupisch and Rothman 2016;Pascual y Cabo 2013; Pascual y Cabo and Rothman 2012; Pires and Rothman 2009;Putnam and Sánchez 2013;Rothman 2007;Scontras, Fuchs and Polinsky 2015). These newer approaches argue that differential ultimate attainment in the HL is not a case of incomplete acquisition, but rather reflects alternative developmental paths that arise because of the variation HSs confront related to key factors that contribute to monolingual conformity.…”
Section: Definition Of What a Heritage Language (Hl)mentioning
confidence: 99%
See 1 more Smart Citation
“…The intravariability in HSs has been investigated by several authors [5,12,14,16], among others. Some of the differences in linguistic proficiency in given groups of HSs may be due to differential literacy levels in the heritage language, and to the degree of its use at home and in social contexts [17].…”
Section: Introductionmentioning
confidence: 99%
“…In general, HSs do not receive a formal education in the heritage language, which delimits the type and contextualization of the linguistic input they receive, especially when compared to speakers from monolingual environments (Rothman 2007, Pires & Rothman 2009. Moreover, the input that HSs receive is mainly provided by speakers who themselves may be undergoing a process of language change (i.e.…”
Section: Introductionmentioning
confidence: 99%